1987
DOI: 10.1073/pnas.84.15.5454
|View full text |Cite
|
Sign up to set email alerts
|

Anti-glycoprotein D antibodies that permit adsorption but block infection by herpes simplex virus 1 prevent virion-cell fusion at the cell surface.

Abstract: Certain monoclonal antibodies specific for glycoprotein D of herpes simplex virus have potent neutralizing activity but fail to block attachment of virus to cells. Here we have investigated the fate of neutralized and infectious virus after attachment to primate cells. Infectious virions fused with the cell surface such that naked nucleocapsids were detectable in the cytoplasm near or just under the plasma membrane. Neutralized virions did not fuse with the cell. They remained attached to the cell surface and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
192
1

Year Published

1989
1989
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(204 citation statements)
references
References 30 publications
11
192
1
Order By: Relevance
“…With the exception of high concentrations of AC1 all MAbs, regardless of neutralizing capacity, were unable to prevent the adsorption of MCMV, a phenomenon that has been observed in other virus systems, including influenza virus (Dimmock, 1984;Possee & Dimmock, 1981), rabies virus (Dietzschold et al, 1987) and herpes simplex virus type 1 (Fuller & Spear, 1987). Our results suggest that MCMV that has been neutralized by antibody can still adsorb to the cell membrane, although infection does not ensue.…”
Section: Discussionmentioning
confidence: 57%
“…With the exception of high concentrations of AC1 all MAbs, regardless of neutralizing capacity, were unable to prevent the adsorption of MCMV, a phenomenon that has been observed in other virus systems, including influenza virus (Dimmock, 1984;Possee & Dimmock, 1981), rabies virus (Dietzschold et al, 1987) and herpes simplex virus type 1 (Fuller & Spear, 1987). Our results suggest that MCMV that has been neutralized by antibody can still adsorb to the cell membrane, although infection does not ensue.…”
Section: Discussionmentioning
confidence: 57%
“…Binding to the cell, and fusion of the viral envelope and the plasma membrane of the cell by which penetration is accomplished (Fuller & Spear, 1987;Lycke et al, 1988;Morgan et al, 1968), includes activities of glycoproteins B, C, D and H (Cai et al, 1988;Campadelli-Fiume et al, 1990;Desai et al, 1988;Kfihn et al, 1990;Ligas & Johnsson, 1988;Muggeridge et al, 1990), but it has not been established whether and how the glycoproteins interact and whether nonglycosylated envelope proteins are involved also in the attachment of the virion to the plasma membrane (Langeland et al, 1990;Spear, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, enveloped viruses (HSV-1, MLV, and VSV-G HIV-1) were able to infect GFP-VCA-positive cells as efficient as GFP-positive cells ( Figures 1E and 2B). In particular, when HSV-1 and ampho MLV enter cells, like HIV-1, the membrane fusion takes place at the cell surface (Fuller and Spear, 1987;McClure et al, 1990;Wittels and Spear, 1991;Nussbaum et al, 1993). These data indicated that the virus-cell membrane fusion was not inhibited by GFP-VCA.…”
Section: The Efficiency Of the Membrane Fusion Is Not Negatively Affementioning
confidence: 99%